2020
DOI: 10.47992/ijmts.2581.6012.0106
|View full text |Cite
|
Sign up to set email alerts
|

Business Architecture Development of Quality Assurance in Higher Education Institutes using TOGAF

Abstract: Recently, quality assurance has attracted widespread attention in higher education institutes in developing countries. Such initiatives mainly focus on standardising higher education while improving the relevance of degree programs. Nevertheless, current quality assurance mechanisms, particularly in developing countries, heavily rely on a document based manual review process. Given the drawbacks associated with such processes, the necessity of technology-based solutions is being recognised. Even though informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In addition, Kotter and Cohen (2012) viewed the change agent as a seeker or supporter of the organization and implementation of the changes and "is able to support leaders to mobilize necessary stakeholder groups and accompany them through the transition" (p. 216). As revealed in their systematic review, Pushpakumara et al (2023) highlighted that stakeholders' involvement is critical to implementing IQA and contributes to maintaining IQA improvement. Following the PDCA model, academics were trained to acquire the required knowledge to develop competence in implementing the IQA practice system (Aburizaizah, 2022), as the PI achievement percentage articulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Kotter and Cohen (2012) viewed the change agent as a seeker or supporter of the organization and implementation of the changes and "is able to support leaders to mobilize necessary stakeholder groups and accompany them through the transition" (p. 216). As revealed in their systematic review, Pushpakumara et al (2023) highlighted that stakeholders' involvement is critical to implementing IQA and contributes to maintaining IQA improvement. Following the PDCA model, academics were trained to acquire the required knowledge to develop competence in implementing the IQA practice system (Aburizaizah, 2022), as the PI achievement percentage articulated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nguyen et al (2021) have made contributions to the literature using peer review, audits and assessments, while Alaskar et al (2019) have stressed the role of the integral involvement of stakeholders to assure quality. In their systematic review, Pushpakumara et al (2023) identified three challenges for maintaining quality assurance work in HEIs: institute-, quality-assuranceprocess-and stakeholder-related. They elaborated that academic involvement is a critical challenge due to their perceptions of quality work as a burden.…”
Section: Student Assessment Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…These systems are not yet integrated with each other, so a proposed business process with 4 applications is proposed that integrates the architectural business IS with company IT. This proposed application is provided to help the company's business processes to more easily achieve the company's vision [38]. The recommended application is a website that is useful for registering forms and displaying the latest product catalogs.…”
Section: Design Business Architecturementioning
confidence: 99%